Increased pain sensitivity in migraine and tension‐type headache coexistent with low back pain: A cross‐sectional population study. (19th January 2018) - Ashina, S.; Lipton, R.B.; Bendtsen, L.; Hajiyeva, N.; Buse, D.C.; Lyngberg, A.C.; Jensen, R.
Abstract: Background: Low back pain is common in the general population and in individuals with primary headaches. We assessed the relative frequency of self‐reported back pain in persons with and without primary headaches and examined pain sensitivity. Method: A population of 796 individuals completed a headache interview based on ICHD criteria and provided data of interest in a self‐administered questionnaire. Headache cases were classified into chronic (≥15) (CH) or episodic (<15 headache days/month) (EH). A total of 495 had a pericranial total tenderness score (TTS), and 494 had cephalic and extracephalic pressure pain thresholds (PPTs) assessed. Results: Adjusted for age, gender, education and poor self‐rated health, 1‐year relative frequency of back pain was higher in individuals with CH (82.5%) and EH (80.1%) compared to no headache group (65.7%). In persons with back pain, TTS was higher in CH, (26.3 ± 12.1) than in EH, (18.5 ± 10.0; p < 0.001) and higher in both groups than in those with no headache, 10.8 ± 8.5 ( p < 0.001 and p < 0.001, respectively). In persons with back pain, temporalis PPT were lower in CH, 169.3 ± 57.8, than in EH, 225.2 ± 98.1, and in no headache group, 244.3 ± 105.4 ( p = 0.02 and p = 0.01, respectively). In persons with back pain, finger PPT were lower in CH, 237.1 ± 106.7, than in EH, 291.3 ± 141.3, or in no headache group, 304.3 ± 137.4 ( p = 0.02 and p < 0.001, respectively). Conclusion: Back pain is highly frequent in individuals with CH, followed by EH and no headache. In persons with CH, back pain is associated with lower cephalic and extracephalic PPTs suggesting central sensitization may be a substrate or consequence of comorbidity. Significance: We found that back pain has high relative frequency in individuals with CH followed EH and no headache. Back pain is associated with low cephalic and extracephalic PPTs in individuals with CH. Central sensitization may be a substrate or consequence of this comorbidity of back pain and CH.